AFRO-ANTILLES IN PORTO VELHO, BRAZIL: HISTORY, CULTURE AND LITERACY - Blackman, Cledenice [UNESP]; Arena, Dagoberto Buim [UNESP]; Antonelli Marcelino Brabo, Tania Suely [UNESP] (Fundacao Univ Tocantins, 2020)
This article makes a brief historical contextualization about the immigration process in the early 20th century from the English Antilles to Brazil, more specifically to Porto Velho. The objective is to analyze how happened the process of acculturation of these immigrants, called here Afro-Antilles, but recognized in the historical text of the region of Rondonia as the Barbadians. In this way, we highlight the relationship between the mother tongue and the Portuguese language in the initial literacy process. The data were obtained from sources such as bibliographies, documents, photos, a questionnaire and a semi-structured interview with two descendants of the community of Porto Velho, Rondonia. The conclusions indicate the confrontation and embarrassment of the research participants as children when they entered schools in the 1940s and 1970s. On the one hand, they came almost or totally literate in English, with the support of the orolity of the dialect bajan, and, another, they went through a new process to learn Portuguese, supposedly to be aerate, but in reality they were learning a foreign language. The progressive process of acculturation of Afro-Antilles and their descendants promoted their cultural rarefaction, the erasure of the dialect, the adaptation of their family names and the loss of cultural identity.
Keywords: Afro-Antilles; Barbadians; Acculturation; Literacy